INDONESIAN STOCK MARKET REACTION BEFORE AND AFTER THE ANNOUNCEMENT OF FIRST COVID-19 CASE - Wijaya, Felia Ananda; Imelda, Elsa (International Journal of Application on Economics and Business, 2023)
This study aims to test whether the event of the announcement of the first confirmed case of COVID-19 in Indonesia on March 2, 2020 affected the Indonesian stock market. A total of 119 samples used in this research event study were taken from the share prices of banks, transportation, and consumer good companies listed on the Indonesia Stock Exchange during the 21-day estimation window. The samples were taken using purposive sampling techniques and then the data was analyzed using the Statistical Package for the Social Sciences (SPSS) ver. 28. One Sample Kolmogorov-Smirnov test is used as a data normality test and hypothesis testing is conducted using the Paired-Sample Wilcoxon Signed Rank test. The results showed that there was no significant difference in the average abnormal return of transportation companies and banks before and after the announcement of the first confirmed case of COVID-19 in Indonesia. Meanwhile the average abnormal return of consumer goods companies showed significant difference before-after the first confirmed case of COVID-19 in Indonesia is announced.